2012
DOI: 10.2298/pan1201037y
|View full text |Cite
|
Sign up to set email alerts
|

Does an undervalued currency merit economic growth?: Evidence from Taiwan

Abstract: Whether an undervalued currency is an attainable industrial policy for developing countries’ sustained development has recently invoked many discussions. This paper studies the case of Taiwan after first determining the misalignment of Taiwan’s currency by estimating the fundamental equilibrium real exchange rate. Three sub-periods for Taiwan’s currency exchange rate misalignment are identified: undervaluation in the periods 1981-1986 and 1998- 2008 and overvaluation during 1987-1997. Second, we use a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…While most empirical studies used panel data that included a cross-section sample with different countries and temporal data with different time periods (Darvas, 2011;Dubas, 2012;Freund and Pierola, 2008;Elbadawi, Kaltani and Soto, 2012;Rodrik, 2008), Yan and Yang (2012) vis-à-vis the US dollar by employing the cointegration method and then the misalignment was determined by calculating the difference between the actual and the estimated equilibrium real exchange rates. They concluded that exchange rate misalignment affected GDP and it mainly came from the third sub-period when the Taiwan dollar was undervalued.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While most empirical studies used panel data that included a cross-section sample with different countries and temporal data with different time periods (Darvas, 2011;Dubas, 2012;Freund and Pierola, 2008;Elbadawi, Kaltani and Soto, 2012;Rodrik, 2008), Yan and Yang (2012) vis-à-vis the US dollar by employing the cointegration method and then the misalignment was determined by calculating the difference between the actual and the estimated equilibrium real exchange rates. They concluded that exchange rate misalignment affected GDP and it mainly came from the third sub-period when the Taiwan dollar was undervalued.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The resulting change in money supply and demand equilibrium affects interest rates, hence allowing for misalignment in exchange rates markets (Branson 1981;Frankel 1983). Though the relationship between real exchange rate misalignment and economic growth exists, there are certain optimal real exchange rate threshold levels at which undervaluing or overvaluing a currency can be associated with either positive or negative economic growth and can directly affect the stock market (Elbadawi, Kaltani and Soto 2012;Yan and Yang 2012;Couharde and Sallenave 2013;Tang 2015).…”
Section: Introductionmentioning
confidence: 99%